The impact of the 21st-Century Maritime Silk Road on sulfur dioxide emissions in Chinese ports: based on the difference-in-difference model - Tian Wang; Guangnian Xiao; Qingjun Li; Salvatore Antonio Biancardo (Frontiers in Marine Science)
The 21st Century Maritime Silk Road (MSR) is a key component of China’s Belt and Road Initiative (BRI), launched in 2013 to enhance global connectivity and foster economic cooperation. By promoting infrastructure development, trade facilitation, and cultural exchange, the MSR seeks to strengthen maritime connectivity, boost regional economic integration, and create new growth opportunities for participating countries. The MSR policy has a positive promoting effect on the economic construction and port development of China’s coastal ports. This study established a difference-in-difference model (DID) to explore the impact of MSR policies on SO2 emissions from coastal and inland ports in China. We searched for panel data from 34 coastal and inland ports in China from 2008 to 2023, and based on this panel data, established a DID model for regression analysis. The regression analysis results indicate that the implementation of MSR policy has a significant positive impact on SO2 emissions from coastal and inland ports in China. Some control variables, such as the total amount of imported goods and domestic emission control area (DECA) policies, also have a significant negative impact on SO2 emissions, while the number of berths, population, and total amount of exported goods have a significant positive impact on SO2 emissions. Based on the regression results of the model, we have proposed some suggestions for port operators and relevant governments to better adapt to MSR policies, promote economic development and environmental protection of ports.